Bias-plasma Assisted RF Magnetron Sputter Deposition of Hydrogen-less Amorphous Silicon. (December 2015) - Gerke, Sebastian; Hahn, Giso; Job, Reinhart; Terheiden, Barbara
Abstract: The execution of special hydrogen diffusion experiments requires an initially hydrogen-free drain layer. Hydrogen-free amorphous silicon (a-Si) deposited by radio frequency magnetron sputter deposition (RFSD) serves this purpose. RFSD yields a rough surface of the film but this can be flattened by an additional post-hydrogenation step. Weak Si-Si bonds are reorganized by hydrogen and the surface becomes smoother. However, by post-hydrogenation the a-Si layer loses its hydrogen-free characteristic. Bias-plasma assisted RFSD offers the possibility of a direct deposition of hydrogen-free a-Si films that exhibit a smooth surface. In this way an amorphous network with only few vacancies and related defects can be achieved as a consequence of the reorganization of weak Si-Si bonds during bias-plasma assisted deposition. Using a crystalline silicon wafer as base substrate for deposition the bias-plasma can additionally be used to prepare the c-Si surface whereby the HF-dip for removing native oxide can be omitted. The optimal deposition temperature of RFSD without bias-plasma, with respect to surface passivation, is ∼325 °C. Bias-plasma assisted RFSD leads to an additional interaction of atoms on the surface of the growing a-Si layer with atoms in the bias-plasma. This interaction decreases the optimal deposition temperature to ∼275 °C. Furthermore, the bias-plasma related flattening of the a-Si surface yields higher passivation quality of post-hydrogenated thin layers (≤ 40 nm) while the formation of additional ion induced defects decreases the passivation quality of thick (>> 40 nm) a-Si layers.